Guía didáctica para la enseñanza de matemática en el octavo año de educación básica de la unidad educativa República del Perú del periodo 2012 - 2013. - Anguisaca Pañafiel, Lipsi Katherine (2015)
This research aims to demonstrate and explain the benefits of the tutorial as teaching resources in the exercise of teaching practice, to achieve the improvement of the learning process teaching, since the incorporation of teaching resources is fundamental in the educational activities, and to facilitate cognitive development of adolescents and thus to improve learning levels. As the process of learning a direct and active relationship between teachers and young people, it has designed a teaching guide that facilitates the teaching process, since it is imperative stimulation of mind for capacity building and skills development in adolescents , so the incorporation of methods, techniques and strategies coherently designed and inserted in the practical guide, so that its application in learning activities fall within the didactic recommendations require that educational conditions in the eighth year of promoting Basic education.